ANALISIS MANAJEMEN RISIKO TERHADAP PEMBIAYAAN BERMASALAH MENURUT ATURAN HUKUM POSITIF DAN HUKUM ISLAM - Hana Melinda; Irvan Iswandi (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This study discusses the Risk Management Analysis of Problematic Financing According to Positive Legal Rules and Islamic Law at Bank Jabar Banten Syariah, Patrol. The focus of the research is the causes of problematic financing and risk management implemented by Bank Jabar Banten Syariah Patrol in tackling problematic financing according to the rules of Positive Law and Islamic Law. This study uses a qualitative method. The data sources used are primary data and secondary data with data collection techniques, namely observation, documentation and interview methods. The analysis in this research is descriptive analysis with data reduction, data presentation and data conclusion. Based on the results of the study, it can be concluded that risk management of problem financing at Bank Jabar Banten Syariah is based on Positive Law, namely the Application of Risk Management regulated under the provisions of the Financial Services Authority Regulation number 65/POJK.03/2016 dated 28 December 2016 concerning Application of Risk Management for Islamic Commercial Banks. And based on Bank Indonesia through the Decree of the Board of Directors of Bank Indonesia Number 31/147/KEP/DIR dated 12 November 1998, it provides a classification regarding credit quality, whether the credit provided by the bank includes non-performing loans or non-performing loans. Based on the view of Islamic Law regarding financing explained in the Qur'an, namely QS.al-Hadid (57): Verse 11, QS. Al-Baqarah (2): Verse 245, and QS. al-Muzzammil (73): Verse 20, Hadith of the Prophet, Ijma', DSN Fatwa About al-Qardh No:19/DSN-MUI/IV/2001 Fatwa of the National Sharia Council and settlement of problematic financing implemented al-Ibra' (debt waiver) recommended in QS. al-Maidah (2): Verse 2.